Interannual and seasonal variations in carbon exchanges over an alpine meadow in the northeastern edge of the Qinghai-Tibet Plateau, China - Wu, Jinkui (PLoS One, 2020)
The alpine meadow is highly sensitive to global climate change due to its high elevation and cold environment. To understand the dynamics of ecosystem carbon cycling, CO(2) fluxes were measured over the Suli alpine meadow, which is located at the upper reach of the Shule River basin at the northeastern edge of the Qinghai-Tibet Plateau (QTP), China. The measurements were taken from October 2008 to September 2012 using the eddy covariance technique. Obvious seasonal and inter-annual variations were observed in the CO(2) flux. The annual net carbon exchange ranged from -195.28 g·CO(2)·m(-2) to -118.49 g·CO(2)·m(-2), indicating that the alpine meadow ecosystem in this area played a role as a carbon sink. The inter-annual variability in the net carbon exchange was significantly related to the length of the growing season for the alpine meadow. The results showed that the months of June, July and August were the strongest CO(2) absorption periods, while April, May and October were the strongest CO(2) release periods. The annual net exchanges of CO(2) in the four years were -118.49 g·CO(2)·m(-2), -130.75 g·CO(2)·m(-2), -195.83 g·CO(2)·m(-2) and -160.65 g·CO(2)·m(-2), and the average value was -151.43 g·CO(2)·m(-2). On a seasonal scale, the monthly CO(2) fluxes were largely controlled by temperature. At the annual scale, there was no dominant factor that influenced the interannual variations in the CO(2) flux.